LEFT VENTRICLE FUNCTIONAL STATE IN CHRONIC HEART FAILURE ON THE BACKGROUND OF EXCESS WEIGHT, DEPENDING ON THE LEVEL OF TOTAL CHOLESTEROL AND TRIGLYCERIDES - Bidzilya, P. (World of Medicine and Biology, 2016)
One of the main links in the pathogenesis of development and progression of chronic heart failure (CHF) is a violation of the functional state of the myocardium and lipid metabolism. More and more studies show paradoxical changes in lipid metabolism in patients with CHF, which manifests the worst course and outcome of the disease at a lower concentration of lipids. On the other hand high cholesterol is accompanied by better survival of patients with CHF of both ischemic and non-ischemic genesis. Such changes are called "the paradox of lipids" or "cholesterol paradox". Overweight and obesity are independent risk factors for development and progression of CHF too, but is also well known that a high body mass index (BMI) is associated with reduced mortality – the "obesity paradox". Recently a limited number of studies that examine the influence of lipid content on the functional state of the myocardium in CHF, the further spread of overweight and obesity, which makes the chosen direction of research, timely and relevant. Research objective: To study the left ventricle (LV) functional state in CHF on the background of excess weight, depending on the level of total cholesterol (TCL) and triglycerides (TG). Material and methods: 220 patients were examined and analyzed 76 case histories of patients of with CHF of I–III functional class on the background of overweight and obesity I–III degree. The diagnosis of CHF installed according to WHO criteria, the European society of cardiology and the Association of cardiologists of Ukraine, FC classified according to functional classification of New York Heart Association (NYHA). Etiologic factors of CHF were chronic forms of IHD, arterial hypertension, and/or a combination of both. Using the BMI was found normal, overweight, and the degree of abdominal type of obesity. Biochemical method was used to determine the blood levels of TCL and TG. With doppler-echocardiography the functional state of LV investigated. Results: It is established that a lower TCL and TG are accompanied by a higher functional class of CHF, distribution and deepening of LV systolic dysfunction and pulmonary hypertension. Significant differences in indices of LV diastolic function, depending on the level of TCL and TG was not observed. At high TG levels availability of significant prevalence of speed of late diastolic filling simultaneously with no significant lower ratio of speed of early and late diastolic filling confirms the trend towards a more profound manifestations of LV diastolic dysfunction. Conclusions: Lower values of TCL and TG in patients with CHF on the background of overweight and obesity are associated with more impaired LV functional state.